Landfill Leachate Treatment By Coagulation Flocculation Using Tween80 - Daud, Nur Aina Syamilah (Universiti Sains Malaysia, 2022)
A landfill may include a number of leachate components that are very toxic, corrosive, acidic, and pollute the environment. These leachates are also distinctive in that they are very changeable and include considerably higher quantities of waste-derived unwanted material. This study was to investigate the treatability of the semi-aerobic landfill leachate via coagulation-flocculation using surfactants. The leachate at Pulau Burung Sanitary Landfill (PBSL) in Penang was chosen as the study location. The impact of pH and coagulant dosage on the removal of chemical oxygen demand (COD), turbidity, and zinc was investigated utilising jar test equipment. A series of jar tests were performed, beginning with 1 minute of rapid mixing at 250 rpm, followed by 5 minutes of slow mixing at 50 rpm, and 30 minutes of settling. Based on the results, chemical oxygen demand (COD) gives a concentration of 3307 mg/L and a BOD5/COD of 0.07, therefore, leachate from PBLS may be categorised as stabilised leachate. The zeta potential and particle size measurement also were discussed in this study. According to the results, pH 2 is very effective at removing COD and zinc, whereas pH 12 is effective at removing turbidity. This study demonstrated that pH adjustment played a significant role throughout the coagulation and flocculation processes, particularly in particle aggregation or disaggregation.